A objetividade dos juízos éticos a partir de Wittgenstein - Ribas, Marcelo Ferreira (2020)
Ethical judgments, informed by moral values, guide the subject’s actions because they are objective, configuring instances that are independent of subjective deliberations. However, the status of objectivity of moral language is controversial and, for this reason, the work aims to clarify it from the conceptual apparatus of Wittgenstein, which ends up showing a conception of objectivity specific to this discourse, based on objective moral certainties. Thereby it opens up to understanding of how the objective ethical judgments work in moral language games, emphasizing the grammatical rules that condition the production of meanings within a form of life. In this context, ethical conceptions develop, which sometimes conflict with each other; however, the differences can be overcome in view of the consensus that can be obtained through persuasion. For all the above, and in the wake of Wittgensteinian philosophical thought, the dynamics of research emphasizes that ethical experience is organized in language and that, through it, it can be understood as an important dimension of constituting meaning for human existence.